2012
DOI: 10.1016/j.ccr.2012.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Accessories to the Crime: Functions of Cells Recruited to the Tumor Microenvironment

Abstract: Mutationally corrupted cancer (stem) cells are the driving force of tumor development and progression. Yet, these transformed cells cannot do it alone. Assemblages of ostensibly normal tissue and bone marrow-derived (stromal) cells are recruited to constitute tumorigenic microenvironments. Most of the hallmarks of cancer are enabled and sustained to varying degrees through contributions from repertoires of stromal cell types and distinctive subcell types. Their contributory functions to hallmark capabilities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
3,138
0
50

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,772 publications
(3,328 citation statements)
references
References 168 publications
25
3,138
0
50
Order By: Relevance
“…The tumor could tactically solve this dilemma thanks to its unique TME with two distinctive features—pro‐tumor growth and immunosuppressive 17, 18, 46, 47. Thus, we assumed that re‐creation of analogous TME would provide the proper ground to support xenograft cells to grow in the host body.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor could tactically solve this dilemma thanks to its unique TME with two distinctive features—pro‐tumor growth and immunosuppressive 17, 18, 46, 47. Thus, we assumed that re‐creation of analogous TME would provide the proper ground to support xenograft cells to grow in the host body.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that tumors consist not only of malignant cells but also of various stromal cell types (Lewis et al, 1995;Hanahan and Coussens, 2012). The stromal cells in cancer can be divided into three subtypes: angiogenic vascular cells (AVCS), infi ltrating immune cells (IICs), and cancer-associated fi broblastic cells (CAFs) (Hanahan and Coussens, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that tumors consist not only of malignant cells but also of various stromal cell types (Lewis et al, 1995;Hanahan and Coussens, 2012). The stromal cells in cancer can be divided into three subtypes: angiogenic vascular cells (AVCS), infi ltrating immune cells (IICs), and cancer-associated fi broblastic cells (CAFs) (Hanahan and Coussens, 2012). Tumor growth is clearly dependent on angiogenesis, as tumors need to establish a blood vessel network to access oxygen and nutrients (Millan Nunez-Cortes, 1991;Cristofanilli et al, 2002;Folkman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…While the distinct functional characteristics of the various CAF subsets are poorly defined, their role in supporting tumour growth has been established: CAFs have been found to promote tumour growth by directly stimulating tumour cell proliferation via secreted growth factors, and by enhancing angiogenesis [17][18][19]. Enhancement of tumour angiogenesis by CAFs can be mediated either directly, by secreting pro-angiogenic factors including interleukin (IL)-8/CXCL8, vascular endothelial growth factor (VEGF), and fibroblast growth factor (FGF)-2, or indirectly, by secreting extracellular matrix (ECM)-remodelling proteases, such as matrix metalloproteinase (MMP)-9, MMP-13, and MMP-14 that activate a multitude of latent soluble and insoluble factors with diverse activities [7,[20][21][22]. In addition, CAFs foster tumour progression and metastasis by modifying the architecture of the ECM, by enhancing deposition of collagen, and by mediating increased cross-linking of collagen fibres, thus stiffening stroma.…”
Section: Introductionmentioning
confidence: 99%